The Investment Behavior of Female Board in Indonesia - Joni; Carolina, Yenni; En, Tan Kwang (Universitas Negeri Semarang, 2024)
This study examines the impact of the presence of female board members on corporate investment behavior in developing countries, such as Indonesia. We selected companies listed on the Indonesia Stock Exchange from 2015-2019. In order to estimate the primary model, the regression model is developed by Ordinary Least Square (OLS) using 1,523 observation data. The results show that increasing the number of female board members can improve investment efficiency. The presence of female commissioners in the dual board mechanism enhances its monitoring function, affecting operational efficiency reflected in investment efficiency. The results from additional tests using the proxy of the percentage of female board commissioners are also consistent. The findings of this study have important implications for academics and practitioners developing a dual board governance system in Indonesia and for understanding the impact of gender diversity on corporate financial outcomes. This study is unique in that it focuses on the Indonesian context, where the role of women at the top management level is still limited and characterized by a dual board system that separates operational and supervisory functions.